2022
DOI: 10.1093/ejcts/ezac014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and haemodynamic variables associated with intensive care unit length of stay and early adverse outcomes after the Norwood procedure

Abstract: OBJECTIVES This study was performed to determine the clinical and haemodynamic variables associated with early adverse outcomes after the neonatal Norwood procedure. METHODS Patients who underwent the neonatal Norwood procedure between 2001 and 2019 were included. The patient diagnosis, morphological characteristics and haemodynamic parameters were analysed to identify factors associated with length of stay (LOS) in the inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Our results demonstrated that the early hemodynamic variable like VIS and MAP might be associated with LOS in ICU. The early hemodynamic variables such as systolic arterial pressure, diastolic arterial pressure and serum lactate level are strong predictive marks of LOS in ICU after the Norwood procedure [15]. There is signi cant right atrial and right ventricular volume overload, the left atrium is frequently small and the left ventricle compressed by the dilated right ventricle in TVPVC [7].…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrated that the early hemodynamic variable like VIS and MAP might be associated with LOS in ICU. The early hemodynamic variables such as systolic arterial pressure, diastolic arterial pressure and serum lactate level are strong predictive marks of LOS in ICU after the Norwood procedure [15]. There is signi cant right atrial and right ventricular volume overload, the left atrium is frequently small and the left ventricle compressed by the dilated right ventricle in TVPVC [7].…”
Section: Resultsmentioning
confidence: 99%
“…Our results demonstrate that early hemodynamic variables, such as VIS and MAP,may be associated with LOS in the ICU. Early hemodynamic variables such as systolic arterial pressure, diastolic arterial pressure, and serum lactate level have been shown to be strong predictive markers of LOS in the ICU after the Norwood procedure [ 16 ]. In TAPVC there is significant right atrial and right ventricular volume overload, the left atrium is frequently small, and the left ventricle is compressed by the dilated right ventricle [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of inter-stage mortality has been reported to be up to 12% in a multicenter trial [4]. Previous studies have identi ed several pre-and postoperative variables as risk factors for interstage mortality [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%